The view from Malakand : Harold Deane's 'Note on Udyana and Gandhara' - Morgan, Llewelyn, (ACT-field school project reports and memoirs, archival studies ;, 2022)
This volume presents a seminal and pioneering account of the antiquities of Swat and Peshawar (Pakistan) by Harold Deane, discovered in the fort at Malakand, Swat; it presents and transcribes the manuscript and provides extended notes identifying and describing the places that Deane discusses in his article.